THE POTENTIAL OF RIBA IN SHARIA GOLD PAWNING - Fajri AF, Muh Shadiqul; Hamid Habbe, Abdul; Wahab, Abdul (Dinasti International Journal of Digital Business Management, 2021)
The practice of Islamic gold pawning in Islamic financial institutions that is in demand by many people in Indonesia has the potential to be included in the practice of usury. The practice of usury is meant to occur because of the merger of qardh and ijarah contracts. This is strictly prohibited in the practice of economics in Islam. This article aims as a critique of the DSN-MUI fatwa No. 26 of 2002 concerning Gold Pawning which allows the merging of qardh and ijarah contracts. Basically, the collection of fees on the qardh contract is allowed for costs that are clearly needed and do not become a profit for Islamic financial institutions. This type of research is descriptive-qualitative with a literature study approach with data sources, namely secondary data obtained from previous studies, and other reference sources.